2009
DOI: 10.4103/0972-6748.57852
|View full text |Cite
|
Sign up to set email alerts
|

Impact of doctor-patient communication on preoperative anxiety: Study at industrial township, Pimpri, Pune

Abstract: Background:Anxiety may not be recognized by physicians though they affect a large number of patients awaiting surgery as reported in some studies. Good doctor-patient communication may have an impact on preoperative anxiety.Aim:To find out the incidence of anxiety in patients awaiting surgery and its association with good doctor-patient communication.Materials and Methods:The study was undertaken in a medical college hospital situated in an industrial township, for the duration of two months. It was a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…11 In a study with 79 patients in India, the prevalence of pre-operative anxiety was 45.7%. 12 But in our study, the prevalence was 31% which is lower than these reported studies.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…11 In a study with 79 patients in India, the prevalence of pre-operative anxiety was 45.7%. 12 But in our study, the prevalence was 31% which is lower than these reported studies.…”
Section: Discussioncontrasting
confidence: 81%
“…11 Well-informed patients are less anxious. 12 Preoperative anxiety among adults is an under-reported problem in India and only a few studies have addressed the issue. 13 The Amsterdam preoperative anxiety and Information scale is a validated tool for measurement of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Study done in Pimpri, India, teaching hospital indicated that patients who were well informed about the surgical procedure in advance had significantly less preoperative anxiety than those unaware of the procedure [ 33 ]. This is consistent finding with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Anesthetic challenges on account of preoperative anxiety include difficult venous access, delayed jaw relaxation and coughing during induction of anesthesia, intraoperative autonomic fluctuations along with increased pain, and nausea and vomiting in the postoperative period. [67] There are also increased anesthetic requirement, prolonged recovery, and prolonged hospital stays.…”
Section: Introductionmentioning
confidence: 99%